ANALISIS PENGARUH TENAGA KERJA, BAHAN BAKU DAN TEKNOLOGI TERHADAP NILAI PRODUKSI PADA INDUSTRI PERCETAKAN DI PROVINSI RIAU - Budiman '; Hainim Kadir; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the analysis of the Labor, Material and Technology Variable to the Production Value in the Printing industry in the Riau . The data used in this study was a time series data from 1990 to 2012 were sourced from Statistic Center agency (Badan Pusat Statistic). This study used quantitative research methods, and analyzed by using multiple linear regression analysis by using SPSS 21 software program for Windows computers. In this study, the independent variable was Labor (X1), Material (X2) and Tecnology (X3) while the dependent variable was Production Value in the Printing industry (Y).This study tested the hypothesis of regression coefficient (coefficient of determination, a significant test concurrent / F test, and the significant individual test / t test). The result showed the variable Labor, Material and Technology at once / simultaneously had a significant influence on the Production Value in the Printing industry. The individual test / partial showed that Labor and Material variable acquired that contributes greater than the variable Technology to the Production Value in the Printing industry.Keywords: Labor, Material, Technology and Production Value in the Printing industry.